Ureteropyeloscopic anatomy of the renal pelvis of the horse. (December 2013) - Pasquel, S. G.; Agnew, D.; Nelson, N.; Kruger, J. M.; Sonea, I.; Schott, H. C.
Summary: Reasons for performing study: Although the equine renal pelvis and terminal recesses have been described post mortem, little information exists about the endoscopic appearance of these structures in the living horse for guiding ureteropyeloscopy. Objectives: To further document the anatomy of the upper urinary collecting system, specifically the renal pelvis and terminal recesses, of the horse. Study design: Descriptive study of cadaver material. Methods: Kidneys were harvested from 10 horses. Magnetic resonance imaging was performed after distension of the renal pelvis with an elastomer casting material, followed by visual inspection of corrosion casts. Transurethral ureteropyeloscopy of the upper urinary tract was performed in 4 horses, followed by histological and immunohistochemical examination of the renal medulla and pelvis of 3 animals. Results: The equine renal pelvis was confirmed to be a funnel‐shaped cavity, flattened dorsoventrally in the craniocaudal direction. Multiple papillary ducts (PDs) from the central part of the kidney open along a ∼3 cm long renal crest that protrudes into the renal pelvis, while PDs from each kidney pole open into 2 long (5–10 cm), narrow terminal recesses that terminate near either end of the renal crest. Openings of the terminal recesses narrow at their junction with the renal pelvis and could be visualised during ureteropyeloscopy in all horses. Minor anatomical variation of the renal crest and terminal recess openings was observed. Conclusions: Current endoscopic equipment can be used to visualise the renal pelvis but could not be advanced into the terminal recesses. The findings of this study will help guide future diagnostic and therapeutic ureteropyeloscopy.